Propuesta de un plan de comunicación corporativa para fortalecer la imagen institucional externa del Centro Cultural Metropolitano de Quito, entidad adscrita al Municipio del Distrito Metropolitano de Quito - Cruz Betancourt, Johanna Verónica (2012)
The Metropolitan Cultural Center (CCM) is a public cultural institution created with the aim of promoting the encounter between different cultures for the permanent construction of identity, knowledge, appreciation and conservation of heritage, located in one of the most valuable buildings historic capital and the country. According to their statistics, receives an average of 3000 hits a day, however, an analysis and investigation of its external environment has shown that a significant percentage of visitors does not recognize the Metropolitan Cultural Center in charge of cultural management is performed, because to have his name and visual identity are largely unknown to the public. With the introduction of this paper proposes the implementation of a Corporate Communications Plan at the Metropolitan Cultural Center, to strengthen its external corporate image and get more contact with society and leadership. So as to generate a value of attachment and loyalty to the institution and thus be viewed as relevant icon in the history of the capital and the country.